Approximation Method for Fixed Point Problem and Variational Inequality Problem without Assumption on the Set of Fixed Pint and the Set of Variational Inequality: Atid Kangtunyakarn - Team, Support (Thai Journal of Mathematics, 2013)
The purpose of this paper is to prove a necessary and sufficient condition to obtain strong convergence theorem for finding a common element of the set of fixed point problem of nonexpansive mapping and the set of variational inequality problem without assumption F(T)VI(C,A) eq in framework of Hilbert space.